Multifunction rack made from kelempayan (neolamarkia cadamda) / Mohammad Faize Moftar, Nur Hannani Abdul Latif and Nik Hazlan Nik Hashim - Moftar, Mohammad Faize; Abdul Latif, Nur Hannani; Nik Hashim, Nik Hazlan (2014)
Space is a constraint that is beginning to hit people these days, with an ever rising population, the demand for space is only bound to increase with time. To overcome this situation, smaller profiles of furniture are made to convers space, Another way in is to produce a multifunction furniture, Multifunction furniture has been a trend in houses especially people who has live in small spaces. This paper discusses more on the multifunction rack that can be used as a rack and table at economical price, The arrangement of the product can be specified as customer satisfaction and taste, Moreover, Kelempayan (plantation species) had been used in this study as raw materials that suit limited spaces at economic price. A set of questionnaire were evaluated regarding the suitability of material used, handling, ergonomics, spaces, function, commercial value and price, 100 respondents among the lecturers, public person and also students were distributed with the questionnaire, From the questionnaire, it was found that the product was acceptable to all the respondents and the concept of multifunction product that suitable for limited space suitable to be commercialized.